(untitled) (Heritage, 2023)
Although our theoretical consideration of the former churches in the area of Crna Reka is based exclusively on the analysis of the foundations of the churches and indirect observations and analogies, the hitherto sporadic interpretations, based on tradition, are thereby called into question. The historical context, therefore, is important for the goals of recontextualizing the mentioned monuments as well as the continuity of church life. As the thesis was presented that the mentioned two churches belong to the Middle Byzantine period, this issue becomes significant for the assessment of the continuity of Christian culture in the area of Crna Reka. All this points to the need for additional research through archaeological excavations, as well as the historical contextualization of the subject of research. Therefore, our research can be understood as a step in that direction.